E EFEKTIVITAS PELATIHAN “POSITIVE PERSONAL JUDGEMENT” TERHADAP PENINGKATAN SELF-ESTEEM PADA REMAJA PANTI ASUHAN - Louis, Louis Pramudeta Lingga Purnama; Endang, Widyorini (Jurnal Ilmiah Penelitian Psikologi, 2024)
This research aims to determine the effectiveness of "Positive Personal Judgment" training in increasing self-esteem in adolescents living in orphanages. The self-esteem of adolescents who participated in self-esteem training is higher than before attending self-esteem training. Testing the effectiveness of this research was carried out by comparing the pre-test and post-test results of the self-esteem scale which was compiled based on Coopersmith's self-esteem aspects: power, significance, virtue and competence. This research data will be presented in quantitative and analyzed using non-parametric statistical methods in the form of the Wilcoxon signed-rank test. From the results of the Wilcoxon signed-rank test, it shows a Wilcoxon Z value of -4.246 with p=0.000 (p<0.05) with a pre-test mean = 12.09 and a post-test mean = 18.13, so it can be concluded that the self-esteem of adoloscents who have participated in self-esteem enhancement training is higher than before participating in self-esteem enhancement training.